2008
DOI: 10.1111/j.1365-2125.2008.03276.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic analysis for risperidone using highly sparse sampling measurements from the CATIE study

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Risperidone metabolism is affected by blocking CYP2D6 and CYP3A4 (in CYP2D6 poor metabolizers) metabolizing enzymes.• Age affects risperidone disposition and renal function affects elimination of 9-hydroxy-risperidone (primary active metabolite). WHAT THIS STUDY ADDS• The detection of a systematic shift in estimated apparent clearance in the African-American population (it is not clear if there are biological or sociological contributors), and a shift in the clearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 28 publications
5
96
2
Order By: Relevance
“…Furthermore, the distribution of the concentration-to-dose ratios showed an interesting pattern in the sense that patients in the amlodipine group were twice as likely to show C/D levels for RIS and the AM above the median as controls. Although pharmacokinetic parameters showed a high inter-individual variability, which has been detected in other studies as well (Balant-Gorgia et al, 1999;Cabaleiro et al, 2015;Feng et al, 2008), it should be noted that we observed no additional distribution differences regarding plasma concentrations and metabolic ratios of RIS as well as the C/Ds of the active metabolite of RIS (9-OH-RIS) between the groups. To our understanding, the findings presented herein imply a potential inhibiting effect of amlodipine most likely on the CYP3A4/5 mediated metabolism of RIS, leading to significantly higher median values of the concentration-to-dose ratios of RIS, 9-OH-RIS and the AM.…”
Section: Discussionmentioning
confidence: 37%
See 1 more Smart Citation
“…Furthermore, the distribution of the concentration-to-dose ratios showed an interesting pattern in the sense that patients in the amlodipine group were twice as likely to show C/D levels for RIS and the AM above the median as controls. Although pharmacokinetic parameters showed a high inter-individual variability, which has been detected in other studies as well (Balant-Gorgia et al, 1999;Cabaleiro et al, 2015;Feng et al, 2008), it should be noted that we observed no additional distribution differences regarding plasma concentrations and metabolic ratios of RIS as well as the C/Ds of the active metabolite of RIS (9-OH-RIS) between the groups. To our understanding, the findings presented herein imply a potential inhibiting effect of amlodipine most likely on the CYP3A4/5 mediated metabolism of RIS, leading to significantly higher median values of the concentration-to-dose ratios of RIS, 9-OH-RIS and the AM.…”
Section: Discussionmentioning
confidence: 37%
“…regarding the mean age of the different study groups, it appeared plausible that patients under antihypertensive therapy would be older. Consequently, we avoided stratifying for age despite the well-known effect of age on RIS metabolism (Feng et al, 2008). Although the size of the control group is remarkably bigger, we chose not to reduce our control group taking into account the extent of the skewness of the sample distribution.…”
Section: Limitationsmentioning
confidence: 99%
“…Pharmacokinetic analyses from the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) study, by Feng et al [52] found that poor risperidone clearance was clearly associated with the PM status of CYP2D6 [53]. In this study, risperidone and 9-OH risperidone concentration data distinguished CYP2D6 polymorphism-related subpopulations.…”
Section: Studies From Several Research Groups Elucidate the Pharmacogmentioning
confidence: 98%
“…Joint pharmacokinetic (PK) modeling accounts for the uncertainties in the data and allows feedback from the metabolite data to the parent drug data to influence the estimation. Thus, more and more studies now use this approach (2)(3)(4). Also, joint modeling allows to correctly evaluate and predict the impact of drug-drug interactions, and in the case of reversible metabolic systems, it is the only way to properly assess covariate effects.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the issue of structural identifiability, it is important to identify the parameters or "apparent" parameters that can be estimated (3), and for the sake of parameter interpretation or covariate analysis, it might be needed to make some assumptions on the parameters (e.g., fixing one parameter to a given value) (4). Also, instability during the estimation is likely to result in solutions at local minima which may lead to biased parameter estimates and potentially wrong conclusions.…”
Section: Introductionmentioning
confidence: 99%